1981
DOI: 10.1021/ja00416a007
|View full text |Cite
|
Sign up to set email alerts
|

Xenon-nitrogen bonds. The synthesis and characterization of [imidobis(sulfuryl fluoride)]xenon(II) derivatives Xe[N(SO2F)2]2, FXeN(SO2F)2 and [(FSO2)2NXe]2F+AsF6- and the radical .cntdot.N(SO2F)2

Abstract: Zwei neue Xe(II)‐Derivate (III) und (IV), in denen Xe an das N‐Atom eines elektronegativen Liganden gebunden ist, werden durch Umsetzung von XeF2 mit HN(SO2F)2 bei niedrigeren Temp. erhalten.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 1 publication
(1 reference statement)
2
30
0
Order By: Relevance
“…ÀNb onds occur for trigonal planar (sp 2 -hybridized) inorganic nitrogen ligandsd erived from the (FO 2 S) 2 N( imidobis(sulfurylfluoride)) group, that include FXeN(SO 2 F) 2 , [15][16][17] + , [19] the related (CF 3 O 2 S) 2 N( imidobis(sulfuryltrifluoromethyl)) group, which is solely represented by (Xe[N-(SO 2 CF 3 ) 2 ] 2 ), [20] and the sulfur-nitrogen-fluorine cations derived from NSF 3 ,n amely, [ F 4 S=NXe] + [21] and [F 4 S=NXe···NSF 3 ] + . [22] The only examples in which xenon is bonded to sp 3 -hybridized nitrogen are [F 5 Te N(H)Xe]…”
Section: IImentioning
confidence: 99%
“…ÀNb onds occur for trigonal planar (sp 2 -hybridized) inorganic nitrogen ligandsd erived from the (FO 2 S) 2 N( imidobis(sulfurylfluoride)) group, that include FXeN(SO 2 F) 2 , [15][16][17] + , [19] the related (CF 3 O 2 S) 2 N( imidobis(sulfuryltrifluoromethyl)) group, which is solely represented by (Xe[N-(SO 2 CF 3 ) 2 ] 2 ), [20] and the sulfur-nitrogen-fluorine cations derived from NSF 3 ,n amely, [ F 4 S=NXe] + [21] and [F 4 S=NXe···NSF 3 ] + . [22] The only examples in which xenon is bonded to sp 3 -hybridized nitrogen are [F 5 Te N(H)Xe]…”
Section: IImentioning
confidence: 99%
“…Theoretical calculations are also extensively employed to aid the interpretation of the experiments, and to explore the conceivable existence of still uncovered molecules and ions. [8,[14][15][16][17] The first xenon-nitrogen species, FXeNA C H T U N G T R E N N U N G (SO 2 F) 2 , was observed in 1974 by spectroscopic methods, [18] and the related compounds Xe[NA C H T U N G T R E N N U N G (SO 2 [19,20] and Xe[NA C H T U N G T R E N N U N G (SO 2 CF 3 ) 2 ] 2 [21] were subsequently reported. It was, however, only in 1982 that an X-ray crystallographic study of FXeNA C H T U N G T R E N N U N G (SO 2 F) 2 furnished the first definitive proof for the existence of a Xe À N bond.…”
Section: Introductionmentioning
confidence: 99%
“…[22,23] In subsequent years, xenonnitrogen chemistry was considerably expanded, noticeably by Schrobilgen and co-workers, [24][25][26][27][28][29][30][31][32][33] and evidence for novel compounds is still emerging. [34,35] In general, apart from the molecular species FXeNA C H T U N G T R E N N U N G (SO 2 F) 2 , [18,20,22,23] Xe[N-A C H T U N G T R E N N U N G (SO 2 F) 2 ] 2 , [20,24] and Xe[NA C H T U N G T R E N N U N G (SO 2 CF 3 ) 2 ] 2 , [21] the xenon-nitrogen compounds observed in the condensed phase are salts of Xe À N cations and counteranions such as AsF 6 À , Sb 3 F 16 À , and BY 4 À (Y=CF 3 , C 6 F 5 ). The Xe À N cations can be in turn divided into two groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first xenon-nitrogen bond in FXeN͑SO 2 F͒ 2 was reported in 1974 by DesMarteau and LeBlond and up to date this and a few similar compounds seem to be the only examples of Xe-N bonding. [3][4][5][6] In 1979, Turbini et al 7 reported the synthesis of Xe͑CF 3 ͒ 2 with a xenon-carbon bond but its unequivocal spectroscopic characterization is still lacking. During the last few years, a number of compounds with Xe-C bonds have been synthesized and characterized, including ionic compounds (C 6 F 5 Xe) ϩ (C 6 F 5 BF 3 )…”
Section: Introductionmentioning
confidence: 99%